Decreased Expression of Programmed Death Ligand-L1 by Seven in Absentia Homolog 2 in Cholangiocarcinoma Enhances T-Cell–Mediated Antitumor Activity - Zheng, Hao; Zheng, Wen-juan; Wang, Zhen-guang; Tao, Yuan-ping; Huang, Zhi-ping; Yang, Le; Ouyang, Liu; Duan, Zhi-qing; Zhang, Yi-nuo; Chen, Bo-ning; Xiang, Dai-min; Jin, Gang; et al. (Frontiers in Immunology, 2022)
N6-methyladenosine (m6A) has been reported as an important mechanism of post-transcriptional regulation. Programmed death ligand 1 (PD-L1) is a primary immune inhibitory molecule expressed on tumor cells that promotes immune evasion. In addition, seven in absentia homolog 2 (Siah2), a RING E3 ubiquitin ligase, has been involved in tumorigenesis and cancer progression. However, the role of m6A-METTL14-Siah2-PD-L1 axis in immunotherapy remains to be elucidated. In this study, we showed that METTL14, a component of the m6A methyltransferase complex, induced Siah2 expression in cholangiocarcinoma (CCA). METTL14 was shown to enrich m6A modifications in the 3’UTR region of the Siah2 mRNA, thereby promoting its degradation in an YTHDF2-dependent manner. Furthermore, co-immunoprecipitation experiments demonstrated that Siah2 interacted with PD-L1 by promoting its K63-linked ubiquitination. We also observed that in vitro and in vivo Siah2 knockdown inhibited T cells expansion and cytotoxicity by sustaining tumor cell PD-L1 expression. The METTL14-Siah2-PD-L1–regulating axis was further confirmed in human CCA specimens. Analysis of specimens from patients receiving anti-PD1 immunotherapy suggested that tumors with low Siah2 levels were more sensitive to anti-PD1 immunotherapy. Taken together, our results evidenced a new regulatory mechanism of Siah2 by METTL14-induced mRNA epigenetic modification and the potential role of Siah2 in cancer immunotherapy.